Use of the childhood myositis assessment scale to measure disease activity in juvenile dermatomyositis and the possible limitation of patient age. (24th May 2012) - Bradford, R; Ward, G; Kelly, A; Ramanan, A
Abstract : Aims: We aimed to assess the use of the Childhood Myositis Assessment Scale (CMAS) via a retrospective audit in our tertiary rheumatology department. CMAS, our audit gold standard, is internationally validated, included in two recently proposed sets of measures of disease activity in Juvenile Dermatomyositis (JDM). Methods: Physiotherapy and medical notes of all patients diagnosed with JDM from 2005 to 2011 were reviewed recording CMAS scores and other JDM assessment tools including muscle-enzymes and Childhood Health Assessment Questionnaires (CHAQ). Results: Eleven new patients were diagnosed, in-keeping with the incidence of JDM (age range 3-15 years). Most CMAS scores were done by our physiotherapist. All had a CMAS prior to treatment, 73% on the day of diagnosis and all within 2 days of diagnosis. The five younger children (≤5 years) had higher CMAS scores at diagnosis (mean 29) than the six older children (mean 22). Muscle-enzyme results were documented at diagnosis for all (maximum Creatinine Kinase 18100 U/l). All patients had follow-up CMAS. Children living further from the tertiary hospital had less CMAS scores documented (table 1 ). Younger children rarely achieved a maximum CMAS score at follow-up (table 2 ). 9/11 patients had CHAQ data in their notes (scores: 0-1.625) although unexpectedly not dated. Conclusions: This audit confirms that from 2005-2011 our department routinely used CMAS for all JDM patients at diagnosis and follow-up. This involved an important physiotherapist role. The lower number of CMAS scores documented for children living >50 miles away was probably because there were also some done at local hospitals unavailable for this audit. Persistent low scores at follow up for our younger patients may reflect a recently reported finding that ≤5 year olds without JDM are unable to score a maximum CMAS score. We propose a novel CMAS computer game for young JDM patients. CMAS, CHAQ, and muscle-enzymes are now included on a database at each clinic visit and re-audit will be performed in the future.